2014
DOI: 10.2105/ajph.2013.301854
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Injury Mortality Among American Indians and Alaska Natives in the United States, 1990–2009

Abstract: AI/AN persons had consistently higher UI death rates than did Whites. This disparity in overall rates coupled with recent increases in unintentional poisoning deaths requires that injury prevention be a major priority for improving health and preventing death among AI/AN populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…49,50 Unintentional injuries accounted for 41% of all deaths among AI/AN children and was the leading cause of death for all pediatric age groups. 21 AI/AN infants and youths had death rates of unintentional injuries at least double those of White infants and youths. A Morbidity and Mortality Weekly Report on years of potential life lost from unintentional injuries for persons ages 0 to 19 years among all racial/ ethnic groups estimated an average of 890 years of potential life lost per every 100 000 persons aged 0 to 19 years.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…49,50 Unintentional injuries accounted for 41% of all deaths among AI/AN children and was the leading cause of death for all pediatric age groups. 21 AI/AN infants and youths had death rates of unintentional injuries at least double those of White infants and youths. A Morbidity and Mortality Weekly Report on years of potential life lost from unintentional injuries for persons ages 0 to 19 years among all racial/ ethnic groups estimated an average of 890 years of potential life lost per every 100 000 persons aged 0 to 19 years.…”
Section: Discussionmentioning
confidence: 95%
“…18 The unintentional injuries were further stratified for the pediatric age groups and by region according to the external causes of injury, 20 as explained elsewhere in this supplement. 21 …”
Section: Pediatric Mortalitymentioning
confidence: 99%
“…Reporting on Indian Health Service data, Murphy et al. () reported that the overall rate of unintentional injury deaths among AIAN men was greater than that of U.S. men and AIAN women by 2.47 and 2.16 times, respectively. Unintentional injuries include injuries and deaths due to motor vehicle accidents, poisoning, falls, drowning, and fire or burns, all of which are greater in the AIAN population as a whole than those among Whites by 1.5 to 3 times.…”
Section: Health Disparities Among Aian Adolescent and Adult Menmentioning
confidence: 99%
“…Motor vehicle crashes are a leading cause of unintentional injury for American Indian and Alaskan Natives ages 1 to 44 [2]. Across America we also experienced an increase in Unintentional Poisoning, in which overdoses of prescription and illegal drug deaths surpassed unintentional motor vehicle deaths [3].…”
Section: Introductionmentioning
confidence: 99%